An Ectopic Parathyroid Adenoma Mimicking Submandibular Gland on 99mTc-MIBI Parathyroid Scintigraphy. (19th October 2022) - Chen, Meijie; Chen, Song; Li, Xuena; Li, Yaming
Abstract: A 67-year-old woman complained of continuous low back pain for 4 months. She was referred for a 99m Tc-MIBI parathyroid scintigraphy with neck SPECT/CT imaging. The planar images showed no abnormal uptake. However, on the SPECT/CT scan, a soft tissue nodule with high uptake was noted adjacent to the left submandibular gland, mimicking normal submandibular gland uptake. Pathological examination from surgical specimen showed that it was an ectopic parathyroid adenoma.